The Use of Platelet-rich Fibrin (PRF) in Cleft Lip and Palate Patients: A Review Article - Yusra H. Al-Mukhtar; Ziad H. Deleme; Mohanned Younis Hamid (University of Mosul, College of Dentistry, 2024)
The purpose of this review article is to introduce the large number of PRF-related studies that have been published to date in the dental industry to better comprehend the clinical processes where Platelet-rich Fibrin may be used to promote bone and tissue growth as it has been shown that Platelet-rich Fibrin increases platelet and fibrin concentration when placed which in turn will eventually speed up the rate of bone development in grafts and enhance the density of the bone created in the region of cleft palate. According to some, the high concentration of platelets, which contain a range of growth factors, is what causes these biomaterials' effects. In addition, the review will highlight the history of evolution, classification, and protocols for platelet-rich fibrin production. Finally, the application of platelet-rich fibrin in cleft lip and palate patients will be reviewed.